Diversity care (Journal of Parents and Teachers, 2014)
Although attention to diversity is one of the strong points of the educational philosophy underlying the LOGSE, diversity and education in values are some of the most difficult aspects to implement in school life. Despite the flexibility and multiple options in the curriculum, there are still students in classrooms who do not reach the minimum objectives of the area or stage. In this article, we present the various methods that the LOGSE proposes as measures to deal with diversity.
Keywords: education; ESO; student; diversity; LOGSE; methods